COMPARATIVE EFFECT OF INDIVIDUALISED AND COOPERATIVE LEARNING STRATEGIES ON SECONDARY SCHOOL STUDENTS ACHIEVEMENT IN MATHEMATICS (UNIZIK Journal of STM Education, 2025)
The study investigated comparative effect of individualised and cooperative learning strategies on secondary school students’ achievement in Mathematics. It covered the topics of venn diagram, union set, interception set, empty set, mean, media all are under set theorem and measure of central tendency. Two research questions and two hypotheses were used to guide the study and relevant literature were also reviewed. The study adopted quasi-experimental design and the study was carried out in Awka Education Zone in Anambra State. The population of the study comprised of 8,583 SS II Mathematics students from 65 co-education secondary schools in Awka Education Zone. Out of the 65 co-educational secondary schools in Awka Education Zone, six schools were drawn. The sample consisted of 270 SS2 students (100 males and 170 females). The sample was obtained using multi-stage sampling procedure. Fifty Mathematics Achievement Test (MAT) structured from WAEC past question papers was used as instruments for collecting data for achievement. The instrument was subjected to face and content validation. MAT reliability was established using Kudar Richardson 20 (KR-20) which yielded reliability coefficient of 0.81. Mean and Standard Deviation were used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The study revealed that individualised learning strategies are more effective than cooperative learning strategies for student achievement in Mathematics. Male students showed more achievement with both strategies than their females counterparts. Recommendations was that government should support teacher training in individualized strategies and promotion of cooperative methods in the education curriculum to enhance achievement in Mathematics. From the recommendations, conclusions and educational implications were made.
Keywords: Mathematics Achievement, Individualised Learning Strategies (ILS) and Cooperative Learning Strategy (CLS).